2020
DOI: 10.3892/ijmm.2020.4593
|View full text |Cite
|
Sign up to set email alerts
|

XPD inhibits cell growth and invasion and enhances chemosensitivity in esophageal squamous cell carcinoma by regulating the PI3K/AKT signaling pathway

Abstract: Esophageal squamous cell carcinoma (EScc) is a lethal disease due to its high aggressiveness. The aim of the present study was to investigate the role of xeroderma pigmentosum complementation group d (XPd) in the growth and invasion of EScc and to elucidate the potential underlying molecular mechanisms. Western blot analysis and RT-qPcR were used to detect the expression level of XPd in EScc tissue samples and adjacent normal esophageal tissue samples. The pEGFP-N2/XPd plasmid was transfected into human EScc c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Our latest data also showed that PI3K/AKT is closely involved in bupivacaine-induced neurotoxicity [ 7 ]. Furthermore, XPD can inhibit tumor cell growth and invasion by regulating the PI3K/AKT pathway [ 25 ]. The relationship between the XPD and PI3K/AKT pathways in the bupivacaine-mediated oxidative neurotoxicity is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Our latest data also showed that PI3K/AKT is closely involved in bupivacaine-induced neurotoxicity [ 7 ]. Furthermore, XPD can inhibit tumor cell growth and invasion by regulating the PI3K/AKT pathway [ 25 ]. The relationship between the XPD and PI3K/AKT pathways in the bupivacaine-mediated oxidative neurotoxicity is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most aggressive malignancies, ESCC imposes lethal menace on human beings [ 27 ]. Illuminated by the existed knowledge about the implications of HDACs and miRNAs in ESCC, this work was started from the axis of HDAC2 and miR-503-5p with the involvement of CXCL10 in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis assay was conducted as we previously described. 21 Briefly, transfected cells were trypsinized and collected by centrifugation, then resuspended in 500 µL of buffer and incubated with Annexin V-FITC/PI kit for 15 min. The apoptotic rate was detected using a flow cytometer (FACSCalibur, BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%